Optimized fertilization strategy for improving grain yield, nutrient uptake, and fertilizer use efficiency of drip-fertigated winter wheat in Northern Xinjiang, China - He, Shuai; Li, Huaisheng; Wang, Shuhong; Li, Yan; Zhang, Lei; Li, Dongwei (International Journal of Agricultural and Biological Engineering, 2024)
Excessive fertilizer application is common in the management of winter wheat (Triticum aestivum L.) in northwest China. However, this practice does not necessarily guarantee higher wheat yield and also causes a waste of resources and environmental pollution. The N, P, and K fertilizer application rates need to be optimized to reduce the nitrate residue in the soil while maintaining a high wheat yield. Field experiments were conducted in three consecutive growth seasons (2018–2021) on winter wheat in Northern Xinjiang of China with four reduced fertilization (N–P2O5–K2O) rates (FS1: 166–80–30 kg ha−1, FS2: 0–80–30 kg ha−1, FS3: 166–0–30 kg ha−1, FS4: 166–80–0 kg ha−1) and the local fertilization rate (CK: 240–105–38). The results showed that increasing NH4+–N concentrations in the soil over the three growing seasons, while NO3––N concentrations decreased in the later experimental years. High soil NH4+–N concentration and low soil NO3––N residues were observed in FS3. When the control fertilization (CK) was applied, the grains had a higher proportion of N and P, while the N content in grains was relatively low at the high fertilization rate. When the fertilizer supply was insufficient (FS2, FS3, and FS4), the proportion of vegetative organs to the total biomass was relatively low. Lower fertilization rates resulted in higher N, P, and K use efficiencies in 2019–2020 and 2020–2021, in comparison to those at higher rates, while FS2 exhibited the highest fertilizer use efficiency. When fertilization (CK) was sufficient, the dry matter accumulation decreased by 3.33–17.08%, and the harvest index increased by 0.87–47.40%. FS1 had the highest spikes number, which significantly increased by 17.98%, 17.80%, and 9.64% compared with CK during 2018–2019, 2019–2020 and 2020–2021, respectively. In conclusion, a reduction in fertilizer application compared with CK could provide excellent production results. The optimal drip fertigation approach for winter wheat production in the arid regions of northwest China was determined to be the N–P2O5–K2O application rate of 166–80–30 kg ha−1 when comprehensively considering the winter wheat yield, soil NH4+–N, and NO3––N, N use efficiency, P use efficiency, and K use efficiency.